Exploring Zinc-Doped Manganese Hexacyanoferrate as Cathode for Aqueous Zinc-Ion Batteries - Julen Beitia; Isabel Ahedo; Juan Ignacio Paredes; Eider Goikolea; Idoia Ruiz de Larramendi (Nanomaterials, 2024)
Aqueous zinc-ion batteries (AZiBs) have emerged as a promising alternative to lithium-ion batteries as energy storage systems from renewable sources. Manganese hexacyanoferrate (MnHCF) is a Prussian Blue analogue that exhibits the ability to insert divalent ions such as Zn2+. However, in an aqueous environment, MnHCF presents weak structural stability and suffers from manganese dissolution. In this work, zinc doping is explored as a strategy to provide the structure with higher stability. Thus, through a simple and easy-to-implement approach, it has been possible to improve the stability and capacity retention of the cathode, although at the expense of reducing the specific capacity of the system. By correctly balancing the amount of zinc introduced into the MnHCF it is possible to reach a compromise in which the loss of capacity is not critical, while better cycling stability is obtained.